Respuesta :

Answer:

g(x) = (x - 4)^2 - 5, and the vertex is (4, -5)

Step-by-step explanation:

Please, use " ^ " to indicate exponentiation:  g(x) = (x - 4)^2 – 5.  Comparing this to y = a(x - h)^2 + k, we see that h must be 4 and k must be -5.  Thus, the vertex is (4, -5).

Make a table showing several x-values and the corresponding y-values:

x       g(x) = (x - 4)^2 - 5                     (x, y)

0                    (-4)^2 - 5 = 11               (0, 11)

4                (4 - 4)^2 - 5 = -5               (4, -5)